Heterogeneity of respiratory disease in children and young adults with sickle cell disease. Issue 6 (29th November 2017) - Lunt, Alan; Mortimer, Lucy; Rees, David; Height, Sue; Thein, Swee Lay; Greenough, Anne
Abstract : To detect and characterise different phenotypes of respiratory disease in children and young adults with sickle cell disease (SCD), 11 lung function and haematological biomarkers were analysed using k-means cluster analysis in a cohort of 114 subjects with SCD aged between 5 and 27 years. Three clusters were detected: cluster 1 had elevated pulmonary capillary blood volume, mixed obstructive/restrictive lung disease, hypoxia and moderately severe anaemia; cluster 2 were older patients with restrictive lung disease; and cluster 3 were younger patients with obstructive lung disease, elevated serum lactate dehydrogenase and bronchodilator reversibility. These results may inform more personalised management strategies to improve outcomes.